2014
DOI: 10.1186/1754-1611-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lignin derivatives as substrates for laccase-catalyzed scavenging of oxygen in coatings and films

Abstract: BackgroundLignin derivatives are phenylpropanoid biopolymers derived from pulping and biorefinery processes. The possibility to utilize lignin derivatives from different types of processes in advanced enzyme-catalyzed oxygen-scavenging systems intended for active packaging was explored. Laccase-catalyzed oxidation of alkali lignin (LA), hydrolytic lignin (LH), organosolv lignin (LO), and lignosulfonates (LS) was compared using oxygen-scavenging coatings and films in liquid and gas phase systems.ResultsWhen coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 22 publications
4
39
0
Order By: Relevance
“…These results, together with similar observations by previous researchers suggest that the generation of many reactive species is not a determinant factor for enhanced polymerization. Nevertheless, in line with this study, Johansson et al [28] and Nugroho Prasetyo et al [7] noted that laccase-catalyzed reaction resulted in extensive polymerization of lignosulfonates as compared to organosolv and indulin lignins. Generally it can be concluded that the decrease in phenolic groups, fluorescence intensity and simultaneous general increase in treated lignin molecular weight are in line with similar changes observed by previous researchers [14,27].…”
Section: Resultssupporting
confidence: 75%
“…These results, together with similar observations by previous researchers suggest that the generation of many reactive species is not a determinant factor for enhanced polymerization. Nevertheless, in line with this study, Johansson et al [28] and Nugroho Prasetyo et al [7] noted that laccase-catalyzed reaction resulted in extensive polymerization of lignosulfonates as compared to organosolv and indulin lignins. Generally it can be concluded that the decrease in phenolic groups, fluorescence intensity and simultaneous general increase in treated lignin molecular weight are in line with similar changes observed by previous researchers [14,27].…”
Section: Resultssupporting
confidence: 75%
“…Higher percentage of spreading cells (37%) was found when Matrigel fraction was 50%, which was consistent with a previous study of 3D colonoid culture in Matrigel. 13 Although hybrid hydrogel with 50% Matrigel supported more cells to spread and grow, it had poor printability due to the low G′ (Figures. 2(a) and S3(c)).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, a previous study has shown that the growth of intestinal stem cells depends on the amount of Matrigel: the highest efficiency of colonoid formation (33 ± 5%) has been observed when 50% Matrigel is used. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been successfully implemented by the use of laccase (EC 1.10.3.2.). This enzyme crosslinks lignin associated aromatic residues, consequently increasing the molecular weight of the extracted polymer and improving the mechanical and barrier properties . Blends of spruce GGM and carboxymethylcellulose exhibited improved mechanical properties due to crosslinking with laccase .…”
Section: Applications Of Plant Polysaccharide Materials In the Packagmentioning
confidence: 99%